APLIKASI REGISTRASI PENERIMAAN MAGANG ONLINE PADA BANK JAMBI - Lestari, Dewi; Bintana, Rizqa Raaiqa; Budiman, Naufal (ScientiCO : Computer Science and Informatics Journal, 2020)
Internship is an activity carried out by students to plunge directly into the world of work in order to increase experience and improve student abilities as well as a forum for implementing knowledge gained from higher education. PT. Regional Development Bank (BPD) of Jambi City or better known as Bank Jambi is an agency that acts as a development bank, commercial bank, regional cash holder and is one of the sources of regional income. As one of the agencies that provides opportunities for students to be able to carry out internship activities, the registration process and internships acceptance at Bank Jambi are still done manually. In today's increasingly developing era, the registration process can actually be carried out without having to come directly to Bank Jambi to deliver a letter and then wait for confirmation whether students are accepted for an internship at Bank Jambi or not. Likewise, the internship student registration file storage system is still done manually, so this is very inefficient, therefore with this online internship registration aplication it is hoped that it can improve the efficiency of the internship acceptance process at Bank Jambi, as a consideration in taking a decision and as part of information technology-based innovation. Making this aplication using the waterfall method, for the analysis and design stages using an object-oriented methodology using the UML diagram tool. For the analysis phase using activity diagrams and use case diagrams, for the design stage using class diagrams.